UMPSA researcher Dr Aizi develops Synbiotic Booster to enhance Mushroom Yield in Malaysia - Hafizatulazlin, Abdul Aziz (UMPSA, 2024)
GAMBANG, 2 December 2024 – Mushrooms are one of the best sustainable food options due to their numerous medicinal benefits.